Feruloyl esterases: Biocatalysts to overcome biomass recalcitrance and for the production of bioactive compounds. (April 2019) - Oliveira, Dyoni M.; Mota, Thatiane R.; Oliva, Bianca; Segato, Fernando; Marchiosi, Rogério; Ferrarese-Filho, Osvaldo; Faulds, Craig B.; dos Santos, Wanderley D.
Highlights: Critical assessment comparing various strategies for feruloyl esterase valorization. Feruloyl esterases are versatile biocatalysts for the production of hydroxycinnamates. The potential of feruloyl esterases for biotechnological applications is highlighted. Biosynthetic tools for esterification and transesterification of bioactive compounds. Abstract: Ferulic acid and its hydroxycinnamate derivatives represent one of the most abundant forms of low molecular weight phenolic compounds in plant biomass. Feruloyl esterases are part of a microorganism's plant cell wall-degrading enzymatic arsenal responsible for cleaving insoluble wall-bound hydroxycinnamates and soluble cytosolic conjugates. Stimulated by industrial requirements, accelerating scientific discoveries and knowledge transfer, continuous improvement efforts have been made to identify, create and repurposed biocatalysts dedicated to plant biomass conversion and biosynthesis of high-added value molecules. Here we review the basic knowledge and recent advances in biotechnological characteristics and the gene content encoding for feruloyl esterases. Information about several enzymes is systematically organized according to their function, biochemical properties, substrate specificity, and biotechnological applications. This review contributes to further structural, functional, and biotechnological R&D both for obtaining hydroxycinnamates from agricultural by-products as well as for lignocellulose biomass treatments aiming for production of bioethanol and other derivatives of industrial interest.